Uruk, Irak. Wissenschaftliche Forschungen 2019 - van Ess, Margarete (e-Forschungsberichte des DAI, 2019)
Scientific research in Uruk (Southern Iraq) which has been part of the world cultural and natural heritage “The Ahwar of Southern Iraq: refuge of biodiversity and the relict landscape of the Mesopotamian cities“ since 2016, was continued in 2019 in close cooperation with Iraqi authorities. Both the investigation of the city wall erected at the beginning of the 3rd millennium BC and the excavations of a sacral building outside the city wall yielded new results. New aerial photographs were generated and evaluated as a basis for detailed topographic plans and for mapping archaeological remains in the surrounding area. In addition, both the environs survey and the geophysical prospection of the city could be continued. All activities also served the training of local and European junior archaeologists as well as of the field workers.